Violations of Religious Freedom and Belief in West Sumatra: Forms, Actors, and Resolution Patterns - Anjali Sabna; Martalia Martalia; Ismail Halim (Al-Adyan: Journal of Religious Studies, 2025)
This research aims to identify the forms of violations, the actors involved, and the conflict resolution mechanisms related to Freedom of Religion and Belief (FRB) in West Sumatra. This study uses a qualitative method with a documentation approach, sourced from advocacy reports, online media, and interviews with purposively selected informants. Data analysis was conducted thru the stages of reduction, visualization, interpretation, and conclusion drawing. The research results show that FRB violations in West Sumatra are dominated by restrictions on freedom of expression in the form of hate speech, followed by criminal acts against religious activities or places of worship, and pressure to convert to another religion. The most dominant violators come from state institutions, followed by community organizations, religious leaders, and other non-state actors. Minority groups, particularly Christians and Ahmadiyyah followers, are the most vulnerable to violations, although cases also target other social groups more broadly. In terms of conflict resolution, the approach used tends to be dominated by a repressive formal legal pathway, accompanied by community-based mediation mechanisms. However, both approaches have not fully guarantyd substantive justice, especially for minority groups who often find themselves in vulnerable positions. These findings indicate a gap between the normative guaranties of FRB in regulations and their implementation practices at the local level. Therefore, there is a need to strengthen a conflict resolution system that is more inclusive, fair, and based on the protection of human rights.